Population structure and reproductive period of whitebelly prawn Nematopalaemon schmitti (Holthuis 1950) (Decapoda: Caridea: Palaemonidae) on the southeastern coast of Brazil - Almeida, Ariadine Cristine [UNESP]; Fransozo, Vivian [UNESP]; Teixeira, Gustavo Monteiro [UNESP]; Furlan, Michele [UNESP]; Hiroki, Katia Aparecida Nunes [UNESP]; Fransozo, Adilson [UNESP] (Int Science Services/balaban Publishers, 2011)
The population biology of Nematopalaemon schmitti in the Ubatuba region on the northern coast of the state of São Paulo was characterized through analyses of the length-frequency distribution, sex ratio, reproductive period, and juvenile recruitment. The specimens were caught monthly from January 1998 to December 1999, from a shrimp boat equipped with double-rig trawl nets. A total of 1073 specimens were analyzed, and the sex and carapace length (0.1 mm) of each individual were noted. The analyzed specimens consisted of 152 juveniles, 437 adult males, 296 adult females, and 188 ovigerous females (OFs). The monthly distribution of N. schmitti by size classes revealed a stable population structure, with both juveniles and adults continuously present. This population showed a unimodal distribution; however, bimodality was identified in June 1998 and 1999 for males, and June 1998 and July 1998 and 1999 for females, probably related to recruitment pulses of juveniles. Sexual dimorphism was indicated by the presence of females in the larger size classes, probably because of their growth rate. The proportion between males and females differed from 1:1 in certain size classes and seasons of the year (chi(2), p < 0.05); in some situations, the females were more abundant than the males, or vice versa. No significant relationship was detected between the seasonal mean temperatures of the bottom water and the percentages of OFs and young, or for the relationship between these two groups (Spearman, p > 0.05). The continuous presence of OFs and young in the population suggests a pattern of continuous reproduction for N. schmitti in the Ubatuba region.
Keywords: Length-frequency distribution; Sex ratio; Breeding season; Juvenile recruitment